O filozofii prawa Trzeciej Rzeszy na sposób sokratejski: Tadeusza Guza interpretacja nazistowskiej filozofii prawa - Dąbrowski, Karol (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The review deals with Tadeusz Guz’s monograph Filozofia prawa III Rzeszy Niemieckiej [The Philosophy of Law in the Third Reich] published by Towarzystwo Naukowe KUL. The book prompts questions about the responsibility of eminent lawyers for the preparation of the ideological foundations of Nazi crimes as well as their intellectual justification. Influenced by ideology, Hitler’s followers created pseudo-logical constructs. They also failed to transform legal positivism — which Nazism avowedly rejected — into amisconceived iusnaturalism imbued with national-socialist morality. Thus what won in the end was acasuistic post-rationalisation of the Führer’s orders and the Nazi “law” turned out to be uncodifiable and untranslatable into the language of general and abstract legal norms.
Keywords: Trzecia Rzesza; doktryna nazistowska